Kapasitas Lentur Balok Beton Ringan Dengan Penambahan Serat Ijuk - Mufti Amir Sultan; Erwinsyah Tuhuteru; M. Fadli Fajar Abdullah (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
Lightweight concrete is concrete that has a specific gravity that is lighter than ordinary concrete. Lightweight concrete can be interpreted as concrete that has a volume weight between 1400-1850 kg/m3. The use of materials that have a light density in the concrete mix will reduce the overall weight of the concrete, thereby reducing the dimensions of the structure and can reduce structural loads, especially dead loads. Pumice or pumice is an aggregate that is classified as light aggregate. This type of stone is widely spread in the North Maluku region. In this study, pumice stone was used as a coarse aggregate for making concrete, the use of pumice as a coarse aggregate tends to reduce the compressive strength, so fiber fibers were used as an added material to the concrete mixture so that fiber concrete was obtained. . This study uses experimental methods, cylindrical specimens with 15 cm and height 30 cm for compressive strength testing, beam test specimens with a size of 15 cm x 20 cm x 120 cm for flexural strength testing. The reinforcement in the concrete beam is varied with variations of 2 reinforcement, 3 reinforcement and 4 reinforcement. The test results show that the use of palm fiber as an added material for the manufacture of lightweight concrete can increase the compressive strength of concrete by 11.70% against lightweight concrete without fibers. The addition of 4 reinforcement at the bottom of the beam tends to increase the capacity of the lightweight concrete beam by 3.28%.